Das ADHS Kaleidoskop State of the Art und bisher nicht beachtete Aspekte von hoher Relevanz - Häßler, Frank (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2008)
ADHD - new facets and interfaces to other disorders: Attention Deficit / Hyperactivity Disorder (ADHD), with a prevalence of 2-6%, is one of the most common mental disorders in childhood, adolescence and adulthood. Despite national and international guidelines and a variety of publications that is hard to overlook, many relevant questions remain on the diagnostic-therapeutic side, among the cooperation partners involved in the overall treatment concept, and those affected and their relatives. Mental disorders occurring simultaneously or as a result of ADHD, such as bipolar disorders, their therapy, the overlap with epileptic seizures, early developmental disorders, motor phenomena, sexual development, teenage pregnancy, delinquency and personality disorders, as well as legal aspects of ADHD and its therapy with stimulants, alternative treatments Evidence-based procedures, including animal-based procedures and, last but not least, the implications for youth welfare are neglected in almost all standard works. Well-known scientists and experienced representatives of various professions pass on their experiences and recommendations to a broad, interested readership in this work. The "ADHD kaleidoscope" opens up the opportunity for medical, psychological, educational therapists, physiotherapists, creative and occupational therapists, youth and social welfare staff, nurses and teachers, as well as affected persons and relatives, to look beyond the so-called "bigger picture" and to find out more about it to inform the many facets of ADHD.